Number Head Together (NHT) in Teaching Writing in EFL Classroom - Hamdiah, Hidayatul; Yusoff, Nik Mohd Rahimi Nik (Anglophile Journal, 2021)
This article focused on the effectiveness of Number Head Together in teaching writing in the EFL Classroom. The aim of the study was to improve EFL students’ writing. This study was quantitative research and used an experimental design. The population was 30 students and the sample was 15 students. Purposive sampling was used in determining the sample of the study. The writing test was the instrument used to collect the data. The data were analyzed by using descriptive statistics and paired sample t-test to test the hypothesis. The students' instrument was an essay-informed descriptive text. Furthermore, the researchers used pre and post to compare scores before and after implied Number Head Together. The mean score of the pre-test was 49.06 at p = 1.364 and the post-test was 78.40 at p = 1.576 which was higher than 0.05 (as the standard significance level in SPSS). This value showed the differences before and after implementing Number Head Together. Hence, it can be concluded that Number Head Together was significantly effective in teaching writing in the tenth graders of Public Vocational High School (SMKN) 1 Janapria, Indonesia. However, The student's writing improves because in grouping the students able to help each other. Keywords: Number Head Together (NHT), EFL Classroom, Teaching Writing